Characterization of high-molecular weight by-products in the production of a trivalent bispecific 2+1 heterodimeric antibody - Dario A. T. Cramer; Vojtech Franc; Anna-Katharina Heidenreich; Michaela Hook; Mahdi Adibzadeh; Dietmar Reusch; Albert J. R. Heck; Markus Haberger (mAbs)
The development of increasingly complex antibody formats, such as bispecifics, can lead to the formation of increasingly complex high- and low-molecular-weight by-products. Here, we focus on the characterization of high molecular weight species (HMWs) representing the highest complexity of size variants. Standard methods used for product release, such as size exclusion chromatography (SEC), can separate HMW by-products from the main product, but cannot distinguish smaller changes in mass. Here, for the identification of the diverse and complex HMW variants of a trivalent bispecific CrossMAb antibody, offline fractionation, as well as production of HMW by-products combined with comprehensive analytical testing, was applied. Furthermore, HMW variants were analyzed regarding their chemical binding nature and tested in functional assays regarding changes in potency of the variants. Changes in potency were explained by detailed characterization using mass photometry, SDS-PAGE analysis, native mass spectrometry (MS) coupled to SEC and bottom-up proteomics. We identified a major portion of the HMW by-products to be non-covalently linked, leading to dissociation and changes in activity. We also identified and localized high heterogeneity of a by-product of concern and applied a CD3 affinity column coupled to native MS to annotate unexpected by-products. We present here a multi-method approach for the characterization of complex HMW by-products. A better understanding of these by-products is beneficial to guide analytical method development and proper specification setting for therapeutic bispecific antibodies to ensure constant efficacy and patient safety of the product through the assessment of by-products.